Optical Packet and Burst Switched Networks Performance for Time-Dependent Video Traffic - Santos Jr., Etelmar; Coelho, Rosângela F. (Journal of Communication and Information Systems, 2017)
In this paper we study the perfonnance of optical packet and burst switched networks (OSN) to suppmt video traffic with scaling characteristics. The optical buffering generally implemented by fiber delay lines (FDLs) is the main challenge to achieve a full-optical switching architecture. For the analysis the MIGIoo and fBm processes are considered to represent the time-dependent video traffic. These stochastic processes are examined in terms of its video traffic scaling (H), heavy-tail distribution (HTD) and autocorrelation (ACF) characterization. We show that with a small number of FDLs (25-50) of 33.92m each and no wavelength conversion an optical packet switch can achieve performance results similm to a burst architecture. Moreover, the jitter values introduced by these FDLs were lower compared to the jitter requirements of the more demanding video traffic. We also demonstrate that the video traffic scaling degree was not affect by the optical packet or burst buffeting solutions. However, the video traffic tail distribution showed to be the clitical aspect to the optical switches dimensioning and thus the future optical switched network performance